Cardiorespiratory fitness is associated with physical literacy in a large sample of Canadian children aged 8 to 12 years - Lang, Justin J; Chaput, Jean-Philippe; Longmuir, Patricia E; Barnes, Joel D; Belanger, Kevin; Tomkinson, Grant R; Anderson, Kristal D; Bruner, Brenda; Copeland, Jennifer L; Gregg, Melanie J; Hall, Nathan; Kolen, Angela M; et al. (Université d'Ottawa | University of Ottawa, 2018)
Abstract Background The associations between cardiorespiratory fitness (CRF) and physical literacy in children are largely unknown. The aim of this study was to assess the relationships between CRF, measured using the 20-m shuttle run test (20mSRT), and components of physical literacy among Canadian children aged 8–12 years. Methods A total of 9393 (49.9% girls) children, with a mean (SD) age of 10.1 (±1.2) years, from a cross-sectional surveillance study were included for this analysis. The SRT was evaluated using a standardized 15 m or 20 m protocol. All 15 m SRTs were converted to 20mSRT values using a standardized formula. The four domains of physical literacy (Physical Competence, Daily Behaviour, Motivation and Confidence, and Knowledge and Understanding) were measured using the Canadian Assessment of Physical Literacy. Tertiles were identified for 20mSRT laps, representing low, medium, and high CRF for each age and gender group. Cohen’s d was used to calculate the effect size between the low and high CRF groups. Results CRF was strongly and favourably associated with all components of physical literacy among school-aged Canadian children. The effect size between low and high CRF tertile groups was large for the Physical Competence domain (Cohen’s d range: 1.11–1.94) across age and gender groups, followed by moderate to large effect sizes for Motivation and Confidence (Cohen’s d range: 0.54–1.18), small to moderate effect sizes for Daily Behaviour (Cohen’s d range: 0.25–0.81), and marginal to moderate effect sizes for Knowledge and Understanding (Cohen’s d range: 0.08–0.70). Conclusions This study identified strong favourable associations between CRF and physical literacy and its constituent components in children aged 8–12 years. Future research should investigate the sensitivity and specificity of the 20mSRT in screening those with low physical literacy levels.